Análise do processo de compras com relação à promoção da sustentabilidade nas universidades federais do Estado do Ceará - Oliveira, Wesley Lopes (2015)
Several countries have now adopted strategies and methodologies to employ sustainability criteria in their procurement concept which was titled as sustainable procurement. This scenario is derived from the increase in discussions about the impacts caused by the company's model of consumption in general leading to the perception of government as a significant consumer goods and services. In this logic, these initiatives represent a form of guidance to suppliers in promoting more responsible means of production based on consumption seeking sustainable development. This study aims to analyze the buying public regarding the promotion of sustainability in Ceará federal universities, as these institutions are cradle of creation and dissemination of knowledge to society in general. This research is carried out from a qualitative approach, contemplating the use of multiple research methods: desk research of exploratory and descriptive nature of the legislation, bidding procedures and 03 (three) semi-structured interviews which were selected for this procedure managers of departments bidding institutions. As a result it turns out that although a concept already quite widespread, according to current federal law, institutions are still at a very basic level of understanding of the meaning of sustainable public procurement, although there is a procedural flow already formatted and aligned with the rules . These processes require improvement with regard to the assessment of needs by the sectors that require purchases, because of the weakness of the procedure is operated without due care, especially in the specifications of what is sought. Among the opportunities for improvement identified at the new dynamic given to the process which assesses the set of results and result of that acquisition and not only cold numbers on the proposed "lower", showed up shared purchases, which favor a offer more interesting from an economic point of view, beyond the need for effective training of managers demanding sectors within institutions.